Zambia National Framework for Climate Services (NFCS - ZM) - International Water Management Institute (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The National Framework for Climate Services (NFCS) serves as an institutional mechanism to enhance coordination, collaboration, and efficiency among national institutions. Its goal is to strengthen the co-production, customisation, dissemination, and utilisation of science-based weather, water, and climate predictions and services, aligning with the five pillars of the Global Framework for Climate Services (GFCS). The GFCS is supported by the World Meteorological Organisation (WMO) with the mandate to the United Nations Framework Convention on Climate Change (UNFCCC) process and the implementation of the Paris Agreement and Sustainable Development Goals (SDGs).